Utilization of Adsorbent Carbon Coconut Shell for Purification of Used Cooking Oil - Siti Khuzaimah; Norma Eralita (Indonesian Journal of Chemical Analysis (IJCA), 2020)
Cooking oil is one of the primary commodities people need to process food. Repeated use of cooking oil at high-temperature heating produces foul smell that reduces the quality and nutritional value of fried food. Decomposition consists of    negative affects quality, but it also results in unfavorable flavor and reduced nutritional value of fried food. An alternative method to treat used cooking oil is adsorption with carbon made of coconut shells. This research aims to lower the levels of acid and peroxide numbers of used cooking oil by purifying it with activated carbon. The acid number determined using the acidimetric and alkalimetric titration method, while the peroxide number measured using the iodometric titration method. These two methods used to analyze samples of fresh cooking oil, used cooking oil, and used cooking oil treated with activated carbon. Results showed a decrease in acid number 34.1449% the second, 29.4103% the fourth use, and 37.5092% on the sixth use of cooking oil. Meanwhile, acidity reduced by 34.1508% the second use, 29.3883% the fourth use, and 37.5066% the sixth use of cooking oil. It found that peroxide number experienced a decrease in 81.2836% the second use, 85.3674% the fourth use, and 62.2462% the sixth use of purified cooking oil.